"That Power and Privilege Thing": Securing Whiteness in Community Work - Todd, Sarah (Journal of progressive human services, 2011)
In this article, I draw upon written texts and discussions with white community organizers so as to explore how the discourse of community work secure whiteness not as an act of maintaining privilege but as an accepted, unnoticed, and even helpful way of seeing and acting in the world. This is problematic because it creates a space in which there can be ethical white subjects who are able to understand themselves as outside of relations of racism. I suggest that it would be more useful to understand practices in which white people advocate with racialized communities as acts of ambivalence.